Cooperation of Genomic, Transcriptomics and Proteomic Methods in the Detection of Mutated Proteins - Zavadil Kokáš, F; Faktor, J; Vojtěšek, B (Klinicka onkologie, 2019)
BACKGROUND: Current anti-tumour therapy is characterised by high non-specificity due to the diverse nature of tumours, which can significantly reduce its efficiency. The massive development of genomic, transcriptomic, and proteomic methods has enabled the detailed characterisation of individual tumours at the genome, transcriptome and proteome levels. Whole-genome sequencing, whole-transcriptome sequencing and exome sequencing can be listed as examples of genomics and transcriptomics methods. Those methods are suitable for detecting single-nucleotide polymorphisms. In the case of proteomic methods, where a peptide library is available, it is possible to detect mutated proteins in a bio-logical sample. Also important is software that interprets and visualises the results or facilitates conversion between data formats that are specific to the method. The combination of methods can in principle increase the likelihood of detecting new neoantigens and design-specific anti-tumour therapy. AIM: The article primarily describes the bio-informatics analysis of samples using the methods of genomics, transcriptomics and proteomics, and the possible problems which must be considered during the analysis. The article includes a description of TransPEM software designed to convert the results from the analysis of single nucleotide polymorphisms into a peptide library of sequences useful for the detection of neopeptides using proteomic methods. The publication is accompanied by a brief description of the proteomics methods using this peptide library and the summary of its limitations.
Keywords: Mutation; nádory; genomika; Humans; výpočetní biologie; lidé; proteomics; proteom; Software; transcriptomics; Neoplasms; genomics; Genomics; software development; Polymorphism, Single Nucleotide; bioinformatics; Transcriptome; mutace; software; jednonukleotidový polymorfismus; Neoplasm Proteins; transkriptom; nádorové proteiny; Proteome; Computational Biology